Is Orthodontic Treatment with Microperforations Worth It? A Scoping Review - Cinzia Maspero; Annalisa Cappella; Claudia Dolci; Maria Grazia Cagetti; Francesco Inchingolo; Chiarella Sforza (MDPI AG, 2022)
Malformations of teeth and dental arches can produce functional modifications intermingled with esthetic alterations. Children's rehabilitation may be long, requiring multiple interventions. One of the main challenges of contemporary orthodontics is to reduce treatment time by accelerating orthodontic tooth movements. Among the currently used methods, micro-osteoperforations (MOPs) are flapless, minimally invasive perforations that induce a local trauma to the bone, increase healing capacity, and accelerate dental movements. The use of MOPs in orthodontics is spreading but there are no definite and recognized protocols for their application. This scoping review collected the available evidence in the effect of MOPs during orthodontic therapy as compared to current treatments, to summarize the evidence. The guidelines proposed by PRISMA-ScR were followed: original clinical studies carried out from 2010 to 2021 were retrieved by medical databases combining the terms "micro-osteoperforations" and "accelerated orthodontic tooth movement". From a total of 965 articles, nine were finally selected. The studies' aims, designs, methods, measurements, outcomes, and main findings were very heterogenous, with a duration ranging from 4 weeks to 7 months. This included only Class I malocclusion to any malocclusion. It assessed the effects of MOPs coupled with a variety of orthodontic mechanics on either the retraction of maxillary canines, the distalization of maxillary molars, or the modifications on premolar roots. Mostly, variations in the number, location, and timing of MOPs impeded a global assessment. Overall, most of the studies (six out of nine) reported moderately useful effects of MOPs, one was negative, and only two found significant advantages of MOPs over conventional treatment. The review synthesized the available evidence about MOP applications in orthodontics and identified some important gaps in knowledge that could be starting points for a systematic review of the literature. In conclusion, even if MOPs can accelerate tooth movements, the variety of aims and methods of the published research prevents suggestion of their widespread use.